Does lean manufacturing improve firm value?. Issue 4 (2nd May 2017) - Zhu, Xuechang; Lin, Yu
Abstract : Purpose: The purpose of this paper is to examine the effects of lean manufacturing on firm value. In particular, it analyses the effects of R&D investment on the relationship between lean manufacturing and firm value. Design/methodology/approach: In this empirical analysis of the relationship between lean manufacturing and firm value, the authors use a propensity score matching (PSM) with a difference-in-difference (DID) estimator to control selection bias and reduce endogenous problems. They also use the triple difference estimator to explore the role of R&D investment. Findings: The results suggest that the achievement of positive and significant effects of lean manufacturing implementation on firm value for a long time and R&D can accelerate this progress. Research limitations/implications: This study highlights the role of R&D investment in accelerating the achievement of positive effects of lean manufacturing on firm value. However, the results may not be entirely generalizable because the empirical data are based solely on Chinese manufacturing firms. Practical implications: Managers need to perform long-term planning while implementing lean manufacturing and should not over-expect a significant short-term improvement in performance. The authors also recommend that enterprises should pay attention to R&D while implementing lean manufacturing. Originality/value: This paper may be the first study to empirically examine the relationship between lean manufacturing and firm value in China by combining a PSM model with the DID estimator to reduce endogenous problems.